Etude Exploratoire De L’impact Des Systèmes d'Information Sur La Performance À Partir D’une Approche Par Alignement : Cas Des Entreprises Marocaines - Yassine Regragui; Youssef Al Meriouh (European Scientific Journal, ESJ, 2017)
The issue of the assessment of the contribution of the information systems to performance (IS) is an area of investigation which has been explored a little in Morocco. From an academic point of view, it is a matter of going further into the field of investigation by the enrichment of previous studies on the issue of the alignment of IS and the performance of organizations. From a practical point of view, it meets the expectations of businesses by providing answers to the question of contribution of IS in obtaining high-performance results. Based on the model of strategic alignment, a qualitative study of the exploratory character of hybrid type was conducted with thirteen Moroccan companies of different sizes and operating managers in different sectors of activities. This is in a bid to assess the applicability of research including the relevance and inadequacies of constructs in the field. The results of this study allowed us to adapt our research hypotheses to the Moroccan context. As a result, a number of variables have been integrated. These makes it possible to build our final alignment of IS model and phase confirmatory.